A LITERATURE REVIEW: ACTIVITIES OF WOMEN IN ARABIC LITERATURE IN CONTEXT OF ECO-FEMINISM AND INTERTEXTUALITY; AN ANALYSIS OF FADWA TOUQAN' WORK - Dr. Shabana Nazar; Dr. Abzahir Khan; Dr. Karim Dad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
In Arab, numerous critics form the literary background are strong supporters of the view that women's writings should be restricted to memoir domains of marriage, children and home thus refraining them from writing on other topics because they are less knowledgeable than men in other aspects. In this context, many literary figures of Palestine pointed out this flaw of Arab literature discriminating men and women. Paradox, Intertexuality and adoption of Islamic literature have been practiced by Palestinian Intifada poets. Therefore, the underlying paper presents women role in Arabic Literature by exploring the theories of Eco-feminism and Intersexuality as mentioned in contemporary and classical poetry with an emphasis through the work of Fadwa Touqan. It is a review paper and findings of the literature discussion has provided with the conclusion that most of Fadwa's poetry and work roams around the grief and sorrow which Israeli occupation brought to Palestine but she also was successful in highlighting the rights of Arabic women in a male dominant society. She changed her poetry and prose from being restricted to particular topics as she used to do in the beginning of her career in 20th century and revolutionized it towards no set boundaries. Thus, with that passage of time her concepts got rooted deeply in eco-feminism till her death (2003). Further, in example of Intertexuality, Touqan' Intertexuality is basically referred to Quran which shows how she takes her basic education and roots from Islam. It is said that she followed her brother in literature and sung a Qasida (Balladry) on his death (Hakeem, 2014). Since Almighty is the ultimate guide to everything in this world and hereafter, she has used the reference of Nour chapter form Quran.